New concept of specific exercise test in diagnostics of anaerobic endurance in cross-country skiers - Gabrys, T.; Cepulenas, A.; Szmatlan-Gabrys, U.; Mroz, A.; Plewa, M. (Education. Physical training. Sport, 2004)
Skiers` work intensity in a ski race changes and reaction of anaerobic glicose gets active, lack of oxygen and lactate concentration increase in blood when climbing up to the mountain. Interrelation of anaerobic and aerobic processes determines an organism`s physiological reactions to a physical load and to their metabolic maintenance structure. The aim of the research — to determine acute adaptation indices of 16—18-year cross-country skiers performing repeated anaerobic specific purpose physical loads (rolling with roller skis in upland course). The testing of 16—18-year old skiers (7 girls and 6 boys), the members of Poland Youth Team of Skiing, was performed in the second decade of October during a preparatory period. Skiers reached 3 × 450 m (in uplands, the uphill escarpment was 35 ± 2o) by roller skis in sub-maximal intensity. After each reached distance (distance of 450 m covered 3 times) there was 2 min recovery pause and during 30 seconds of the pause a blood test from the finger was taken for determination of lactate concentration. During the test, oxygen uptake (VO2) had been registered incessantly by a portative gas analyzer (R-4, Coemed, Italy). Heart rate (HR) — by a POLAR TEAM sport tester (Polar, Finland). Lactate concentration in the blood was determined 4 min, 8 min and 12 min during recovery after a total test load. Restitution index of heart rate (HR) and VO2 restitution index (Zoladz, 1994) was determined 1 min after each distance. It is determined that skiers reach 450 m at the highest speed during the first test and during other repeats their speed is lower. The highest VO2 indices are achieved reaching 450 m distance for the first time and during each following repeat VO2 indices decrease and lactate concentration in the blood increases. Restitution index of heart rate (HR) and VO2 restitution index of skiers during recovery pauses after repeatable physical loads change ambiguously — for some skiers increase for other — decrease. Presented test programme enables to determine in complex and estimate individual peculiarities of skiers` organism adaptation to specific anaerobic physical load.